On econometric analysis of structural systems with permanent and transitory shocks and exogenous variables - Adrian Pagan; Mohammad Hashem Pesaran (Institute for the Study of Labor (IZA), 2007)
This paper considers the implications of the permanent/transitory decomposition of shocks for identification of structural models in the general case where the model might contain more than one permanent structural shock. It provides a simple and intuitive generalization of the influential work of Blanchard and Quah (1989), and shows that structural equations for which there are known permanent shocks must have no error correction terms present in them, thereby freeing up the latter to be used as instruments in estimating their parameters. The proposed approach is illustrated by a re-examination of the identification scheme used in a monetary model by Wickens and Motta (2001), and in a well known paper by Gali (1992) which deals with the construction of an IS-LM model with supply-side effects. We show that the latter imposes more short-run restrictions than are needed because of a failure to fully utilize the cointegration information.
urn:nbn:de:101:1-20080416296
Keywords: 330; Strukturgleichungsmodell; Schock; Dekompositionsverfahren; Fehlerkorrekturmodell; IS-LM-Diagramm; Theorie